Reconstruction of gene regulatory network related to photosynthesis in Arabidopsis thaliana - Yu, Xianbin; Zheng, Guangyong; Shan, Lanlan; Meng, Guofeng; Vingron, Martin; Liu, Qi; Zhu, Xin-Guang (Frontiers in Plant Science, 2014)
Photosynthesis is one of the most important biological processes on the earth. So far, though the molecular mechanisms underlying photosynthesis is well understood, however, the regulatory networks of photosynthesis is poorly studied. Given the current interest in improving photosynthetic efficiency for greater crop yield, elucidating the detailed regulatory networks controlling the construction and maintenance of photosynthetic machinery is not only scientifically significant but also holding great potential in agricultural application. In this study, we first identified transcription factors (TFs) related to photosynthesis through the TRAP approach using position weight matrix information. Then, for TFs related to photosynthesis, interactions between them and their targets were also determined by the ARACNE approach. Finally, a gene regulatory network was established by combining TF-targets information generated by these two approaches. Topological analysis of the regulatory network suggested that a) the regulatory network of photosynthesis has a property of “small world”; b) there is substantial coordination mediated by transcription factors between different components in photosynthesis.